2012
DOI: 10.1021/ja2108239
|View full text |Cite
|
Sign up to set email alerts
|

Finding MOFs for Highly Selective CO2/N2 Adsorption Using Materials Screening Based on Efficient Assignment of Atomic Point Charges

Abstract: Electrostatic interactions are a critical factor in the adsorption of quadrupolar species such as CO(2) and N(2) in metal-organic frameworks (MOFs) and other nanoporous materials. We show how a version of the semiempirical charge equilibration method suitable for periodic materials can be used to efficiently assign charges and allow molecular simulations for a large number of MOFs. This approach is illustrated by simulating CO(2) and N(2) adsorption in ~500 MOFs; this is the largest set of structures for which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
188
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 196 publications
(191 citation statements)
references
References 40 publications
3
188
0
Order By: Relevance
“…The intrinsic nature of such types of materials makes them have many potential advantages over traditional adsorbents in systematically and precisely modulating their framework topologies and surface chemistry (Stock and Biswas, 2012;Cohen, 2012;Gagnon et al, 2012). Both experimental and theoretical investigations have shown that MOFs can serve as a uniquely ideal platform for the separation of CO 2 from various gas mixtures (Bastin et al, 2008;Couck et al, 2009;Bae et al, 2008;McDonald et al, 2012;Yang et al, 2013a;Burtch et al, 2013;Yazaydın et al, 2009;Liu and Smit, 2009;Haldoupis et al, 2012;Karra and Walton, 2010). However, most of studies available so far are performed to evaluate their performance via PSA/VSA processes (Yang et al, 2011b;Bae and Snurr, 2011;Wilmer et al, 2012;Mu et al, 2010;Pirngruber et al, 2012;Krishna and Van Baten, 2011b), while research efforts are seldom conducted in the scope of TSA approach.…”
Section: Introductionmentioning
confidence: 99%
“…The intrinsic nature of such types of materials makes them have many potential advantages over traditional adsorbents in systematically and precisely modulating their framework topologies and surface chemistry (Stock and Biswas, 2012;Cohen, 2012;Gagnon et al, 2012). Both experimental and theoretical investigations have shown that MOFs can serve as a uniquely ideal platform for the separation of CO 2 from various gas mixtures (Bastin et al, 2008;Couck et al, 2009;Bae et al, 2008;McDonald et al, 2012;Yang et al, 2013a;Burtch et al, 2013;Yazaydın et al, 2009;Liu and Smit, 2009;Haldoupis et al, 2012;Karra and Walton, 2010). However, most of studies available so far are performed to evaluate their performance via PSA/VSA processes (Yang et al, 2011b;Bae and Snurr, 2011;Wilmer et al, 2012;Mu et al, 2010;Pirngruber et al, 2012;Krishna and Van Baten, 2011b), while research efforts are seldom conducted in the scope of TSA approach.…”
Section: Introductionmentioning
confidence: 99%
“…In 2012, Sholl's group [75] used GCMC simulations to calculate adsorption of CO 2 and N 2 in 500 different MOFs. This was the largest set of structures for which this information has been reported until 2012.…”
Section: Large-scale Screening Of Mofsmentioning
confidence: 99%
“…55 The Localization of Properties (LoProp) 56 approach was chosen to compute the point charges. The LoProp approach was also used to extract dipoles, quadrupoles, and polarizabilities.…”
Section: Partitioning Molecular Propertiesmentioning
confidence: 99%